A Systematic Analysis of Human Disease-Associated Gene Sequences In Drosophila melanogaster - Reiter, Lawrence T.; Potocki, Lorraine; Chien, Sam; Gribskov, Michael; Bier, Ethan (Genome Research, 2001)
We performed a systematic BLAST analysis of 929 human disease gene entries associated with at least one mutant allele in the Online Mendelian Inheritance in Man (OMIM) database against the recently completed genome sequence of Drosophila melanogaster. The results of this search have been formatted as an updateable and searchable on-line database called Homophila. Our analysis identified 714 distinct human disease genes (77% of disease genes searched) matching 548 unique Drosophila sequences, which we have summarized by disease category. This breakdown into disease classes creates a picture of disease genes that are amenable to study usingDrosophila as the model organism. Of the 548Drosophila genes related to human disease genes, 153 are associated with known mutant alleles and 56 more are tagged byP-element insertions in or near the gene. Examples of how to use the database to identify Drosophila genes related to human disease genes are presented. We anticipate that cross-genomic analysis of human disease genes using the power of Drosophilasecond-site modifier screens will promote interaction between human andDrosophila research groups, accelerating the understanding of the pathogenesis of human genetic disease. The Homophila database is available at http://homophila.sdsc.edu.
10.1101/gr.169101